Investigation and Detection of Risk Factors Related to the Period without Tobacco Consumption - Alkan, Ömer; Demir, Ayşenur (Addicta: The Turkish Journal on Addictions, 2020)
The consequences of tobacco consumption include disease and death. Many people want to give up tobacco use because of its dangers, but its addictive quality makes it difficult. The aim of this study was to detect the risk factors in Turkey that affect the number of days without tobacco consumption among individuals attempting to quit smoking in the last 12 months. Data collected from 1,251 individuals selected in the Global Adult Tobacco Survey were utilized in this study. The multivariate cox regression analysis was used to determine the factors that affected the number of days without tobacco among individuals aged 15 and above in Turkey. At the end of the analysis, variables, such as gender, education, age, household rules about tobacco consumption, supporting higher taxes for tobacco products, and household welfare indicators, were effective in the tobacco-free period. To prevent smoking relapses, tobacco cessation programs should be promoted among the citizens. Awareness of the risks associated with tobacco consumption should be raised and social support from family and friends to quit smoking should be further accentuated. Tütün Kullanılmayan Süreyle İlişkili Riskli Faktörlerin Araştırılması ve BelirlenmesiTütün kullanımının sonuçları hastalıklar ve ölümlerdir. İnsanlar tütünün zararlarından dolayı bu kullanımlarından vazgeçmek istemektedir ancak tütünün bağımlılık yapıcı özelliği buna engel olmaktadır. Tütün kullanmayı bırakanlarda ise yeniden başlama durumu yaygın olarak görülmektedir. Bu çalışmanın amacı, Türkiye’de tütün kullanımını bırakmayı deneyen bireylerin tütün kullanmadıkları gün sayısını etkileyen risk faktörlerini belirlemektir. Bu çalışmada Küresel Yetişkin Tütün Araştırması’nda seçilen 1.251 kişiden toplanan veriler kullanılmıştır. Türkiye’de 15 yaş ve üzeri bireylerde tütün kullanmadığı gün sayısını etkileyen faktörleri belirlemek için çok değişkenli cox regresyon analizi kullanılmıştır. Analiz sonunda, cinsiyet, eğitim, yaş, tütün tüketimine ilişkin hane halkı kuralları, tütün ürünleri için daha yüksek vergileri destekleme ve hane halkı refah göstergeleri gibi değişkenler tütün kullanılmayan dönemde etkili olmuştur. Sigara içilmesinin önlenmesi için vatandaşlar arasında tütün bırakma programları teşvik edilmelidir. Tütün tüketimi ile ilgili risklerin farkında olunmalı ve sigarayı bırakmak için aileden ve arkadaşlardan gelen sosyal destek daha da vurgulanmalıdır.To
Keywords: Tobacco cessation; Cox regression; Turkey; Global adult tobacco survey; Tobacco use